Development or maintenance? Dual‐oriented human resource system, employee achievement motivation, and work well‐being. Issue 4 (14th October 2019) - Lin, Congcong; Li, Xiufeng; Lam, Long W.
Abstract: Drawing on the person–organization fit theory, this study elaborates a dual‐oriented human resource (HR) system and explores when and how two HR bundles (development vs. maintenance) influence work well‐being. The results of the confirmatory factor analysis with a sample of 1, 946 supervisors from a Chinese high‐tech firm show that the dual‐oriented HR model fits the data better than a holistic HR system. In another study with a multilevel sample of 64 corporate branches and 434 employees, the findings confirm the proposed joint effect of the dual‐oriented HR system and achievement motivation on well‐being. Specifically, development‐oriented HR practices are more positively related to work well‐being only when individual achievement motivation is high; by contrast, maintenance‐oriented HR practices are more positively related to work well‐being only when individual achievement motivation is low. Work meaning mediates these effects. These findings provide guidance on the effective design of HR practices.